Kesulitan Guru SD Negeri Dumeling 01 dalam Mengimplementasikan Penilaian Autentik Selama Masa Pandemi - Nur Atika; Rofian Rofian; Mei Fita Asri Untari (STKIP Andi Matappa Pangkep, 2021)
The purpose of this study is to know the process of implementing online learning in high classes at SD Negeri Dumeling 01 during the pandemic and to know the difficulty factors of teachers of SD Negeri Dumeling 01 high class in implementing authentic assessment of students in pandemic learning. The research method used is a qualitative method with descriptive approach. Data collection in the study was conducted by means of observation, interview and documentation. Data analysis techniques used based on the Miles and Huberman models are data collection, data reduction, data presentation, and data conclusion. The result of this study is that the analysis of the difficulty of high-class teachers of SD Negeri Dumeling 01 in the implementation of authentic assessments in the pandemic is the online learning process used through whatsapp groups by sending teachers materials and assignments. The factors of teacher difficulty in the implementation of authentic assessments during the pandemic are online learning, understanding of authentic assessments that are still low, low creativity of teachers, characteristics of students who are less supportive, lack of authentic assessment training, insufficient time, and lack of school infrastructure.